Household in Sundarban Delta of India: a Participatory Rural Appraisal - Das, S. K.; Tripathi, H. (International Journal of Bio-resource and Stress Management, 2012)
The Gangetic delta, known as Sundarban, is one of the few existing mangrove eco-systems, a largest delta and largest mangrove forest area in the world. Comprises of a number of islands the region is spread over India (one-third) and Bangladesh (two-third). Though well known as one of the biodiversity hotspots in the world, Sundarban is les known from rural sociological point of view. Household constitutes an important part of the physical structure of rural society. Therefore, a study of household in terms of its physical resources can prove valuable for planning suitable developmental strategy. Hence, a study was carried out in four purposively selected villages of Sundarban delta in India to have an idea about the characteristic features of the households. Using case study method of PRA (Participatory Rural Appraisal) data were collected from individuals and groups of villagers through listing, topical interview and observation methods. The in-depth study reveals many things hitherto unknown to the outside world which may help in planning a program for socio-economic development of this unique part of the world where rich resources and poverty paradoxically co-exist.